Luxury values as drivers for affective commitment: the case of luxury car tribes - Loureiro, S. M. C. (2017)
Brand communities have been regarded as avenues where the relationship between consumers and a brand can flourish. The main aim of this research was to investigate if luxury values, that is, the individual, social and functional values and believes influence the affective commitment in the luxury car context. This study explores the effect of luxury values on luxury car affective commitment mediated by brand tribalism and brand reputation. The proposed model was tested through a survey on car brand communities (BMW, Mercedes and Audi). Findings reveal that brand tribalism is more important than brand reputation when developing brand relationship. Functional values are more effective to create brand reputation than to improve brand tribalism. Social values influence more on brand tribalism than on brand reputation. Individual values exercise a significant effect on brand tribalism.